Peningkatan Kemampuan Membaca Pemahaman Menggunakan Model Pembelajaran Talking Stick Siswa Kelas IV SD - Suci, Fitrah; Abidin, Zainal; Mahyuddin, Ritawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The research objective was to describe the improvement of comprehension reading ability using the Talking stick model of the fourth grade students of SD Negeri 06 Piai Tangah, Kota Padang. Research subjects were researchers as practitioners and fourth grade students totaling 31 students consisting of 18 men and 13 women. In prabaca cycle I got an average score of 60.48, the average value when reading 66.53, and the average post-reading value 69.35. In cycle II the average score was 75.81, the average value when reading was 95.56, and the average post-reading value was 77.41. Thus the Talking stick learning model can improve students' reading comprehension skills in class IV SDN 06 Piai Tangah Kota Padang. Keywords: reading understanding, talking stick, elementary students  The research objective was to describe the improvement of comprehension reading ability using the Talking stick model of the fourth grade students of SD Negeri 06 Piai Tangah, Kota Padang. Research subjects were researchers as practitioners and fourth grade students totaling 31 students consisting of 18 men and 13 women. In prabaca cycle I got an average score of 60.48, the average value when reading 66.53, and the average post-reading value 69.35. In cycle II the average score was 75.81, the average value when reading was 95.56, and the average post-reading value was 77.41. Thus the Talking stick learning model can improve students' reading comprehension skills in class IV SDN 06 Piai Tangah Kota Padang. Keywords: reading understanding, talking stick, elementary students